2021
DOI: 10.1177/21514593211059865
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Intraoperative Fractures in Reverse Shoulder Arthroplasty: A Systematic Review

Abstract: Introduction The reverse shoulder arthroplasty is nowadays a treatment option for a variety of shoulder problems. As its incidence rose, also the number of complications increased, including intraoperative fractures. Significance We performed a systematic review and critical analysis of the current literature following the PRISMA guidelines. Our purpose was to: 1) determine incidence, causes, and characteristics of intraoperative fractures; 2) evaluate their current treatment options, possible related complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 164 publications
(184 reference statements)
1
4
0
Order By: Relevance
“…The complications seen in this study are comparable to those reported in the literature for custom glenoid components and revision shoulder arthroplasty, with the relatively high rate of complications reflecting the challenging nature of complex revision surgeries [8]. Complications such as greater tuberosity fracture in both primary and revision cases were recently reported by Wixted et al [28] and Dolci et al [29]. Our complications when using a custom glenoid component are similar to those reported by Rangarajan et al [8], who reported four complications (21%): one greater tuberosity fracture; one humeral perforation requir- Several limitations need to be considered when interpreting the results of this study or considering performing this procedure.…”
Section: Discussionsupporting
confidence: 83%
“…The complications seen in this study are comparable to those reported in the literature for custom glenoid components and revision shoulder arthroplasty, with the relatively high rate of complications reflecting the challenging nature of complex revision surgeries [8]. Complications such as greater tuberosity fracture in both primary and revision cases were recently reported by Wixted et al [28] and Dolci et al [29]. Our complications when using a custom glenoid component are similar to those reported by Rangarajan et al [8], who reported four complications (21%): one greater tuberosity fracture; one humeral perforation requir- Several limitations need to be considered when interpreting the results of this study or considering performing this procedure.…”
Section: Discussionsupporting
confidence: 83%
“…Problems related with locking of the stem are about 5% in our series, this rate is similar to data of the Symposium of the French Orthopedic Society in 2019. Nevertheless, early rehabilitation could explain mobilization of stem or locking screws [11,42]. Main strength of this work remains the follow-up of 45 ± 19 months with a minimum follow-up of 2 years, on a multicenter population of 94 patients, with a single type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 15 years, the number of Reverse Shoulder Arthroplasties (RSA) has increased exponentially as a choice for pain relief, improving shoulder function and implant survival [ 1 ]. Revision rates have been reported between 12% and 16% [ 1 , 2 ], with exceptions reaching 69% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 15 years, the number of Reverse Shoulder Arthroplasties (RSA) has increased exponentially as a choice for pain relief, improving shoulder function and implant survival [ 1 ]. Revision rates have been reported between 12% and 16% [ 1 , 2 ], with exceptions reaching 69% [ 3 ]. Aseptic loosening of the humeral component, and intra- and post-operative bone fracture, are among the ten most common complications potentially leading to revision surgery [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation